CODE SWITCHING USED BY EMILY AS SEEN IN THE EMILY IN PARIS - Theresia Seismika Widowati; Barli Bram (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2021)
Nowadays, being bilinguals when communicating with others is something familiar. Many factors can influence people to be bilinguals at the same time. By being bilinguals, people are urged to do code-switching. This study aims to answer the questions of what types of code-switching are used by the main character of Emily in Paris series and the functions of code-switching that are found in the Emily in Paris series. This study used a qualitative method and the data were collected from the script of episode 1 till episode 10 of Emily in Paris series. The results of the research showed that there were 3 types of code-switching that are used by Emily in Emily in Paris, such as inter-sentential switching, intra-sentential switching, and tag switching. Furthermore, the functions of code-switching that are usually used by Emily were 6, namely reiteration, quotation, addressee specification, interjection, message qualification, and personalization versus objectification.